EVALUATION DE LA PREMIERE EXPERIENCE DE GESTION DELEGUEE DES DECHETS MENAGERS A CASABLANCA, MAROC - Jalila, Ghalloudi; Ghalem, Zahour; Mohamed, Talbi (European Scientific Journal, ESJ, 2015)
Urban expansion, population growth and modes of consumption are all factors that have caused a significant increase in waste production in Casablanca. Privatized in 2004, the solid waste management in this city is confronted with institutional, technical and legal problems. The analysis of documents - the Law 28-00 on solid waste, the Convention of delegated management and the National Program of Household Wastes (NPHW) - allows assessing the institutional, political and technical difficulties of the reform of the solid waste management. It shows, in particular, that the legal provisions and governmental strategies are difficult to be applied. In addition, The investigations carried out in the popular quarters of Ben M’Sik shows that wastemanagement solids is perceived like a shared responsibility.